Question #d48c4

1 Answer
Nov 15, 2016

Answer:

We can simplify to #2root(3)(9) + 4root(3)(3)#.

Explanation:

Start by simplifying everything as much as you can. Remember you are dealing with cube roots.

#=>4root(3)(9) - 5root(3)(3) - root(3)(8 xx 9) + 3root(3)(27 xx 3)#

#=>4root(3)(9) - 5root(3)(3) - 2root(3)(9) + 3(3)root(3)(3)#

#=>4root(3)(9) - 5root(3)(3) - 2root(3)(9) + 9root(3)(3)#

#=>2root(3)(9) + 4root(3)(3)#

We're done here, because everything is irreducible.

Hopefully this helps!